ANALYSIS OF STUDENT MISCONCEPTIONS AND THEIR CAUSES ON PARABOLIC MOTION USING A SIX-TIER MULTIPLE CHOICE - Hidayat, Rahmat (Physics Learning and Education, 2024)
The goal of learning physics in institutions using the 2013 curriculum is to develop a solid conceptual grasp of each subject. Students experience misconceptions while having a solid conceptual grasp that contradicts accepted notions. Learning about parabolic motion might lead to misconceptions, which are common in physics. Teachers need to be aware of the causes in addition to the misconceptions. This study attempts to identify students' misconceptions and determine the root causes of the parabolic motion material. The Six-Tier Multiple Choice Instrument, which has 18 items, was the tool utilized in this study. The sort of research used is descriptive research using the survey method. pupils from class X MIPA MAN in Padang City made up the population of this study, with a total sample size of 514 pupils. Overall, this investigation of the three MANs in Padang City discovered a 28.0% misunderstanding. According to the study's findings, there were 25.8% misconceptions in MAN 3, 29.2% mistakes in MAN 1, and 26.6% misconceptions in MAN 2. With a percentage of 45.4%, students' individual opinions are the primary source of misconceptions.